Barriers and facilitators to the administration of prehospital tranexamic acid: a paramedic interview study using the theoretical domains framework. Issue 7 (11th November 2021) - Goodwin, Laura; Nicholson, Helen; Robinson, Maria; Bedson, Adam; Black, Sarah; Kirby, Kim; Taylor, Hazel; Voss, Sarah; Benger, Jonathan
Abstract : Background: Tranexamic acid (TXA) is an antifibrinolytic drug used to prevent bleeding. It was introduced as an intervention for post-traumatic haemorrhage across emergency medical services (EMS) in the UK during 2012. However, despite strong evidence of effectiveness, prehospital TXA administration rates are low. This study used the theoretical domains framework (TDF) to identify barriers and facilitators to the administration of TXA to trauma patients by EMS providers (paramedics) in the UK. Methods: Interviews were completed with 18 UK paramedics from a single EMS provider organisation. A convenience sampling approach was used, and interviews continued until thematic saturation was reached. Semistructured telephone interviews explored paramedics' experiences of administering TXA to trauma patients, including identifying whether or not patients were at risk of bleeding. Data were analysed inductively using thematic analysis (stage 1). Themes were mapped to the theoretical domains of the TDF to identify behavioural theory-derived barriers and facilitators to the administration of TXA to trauma patients (stage 2). Belief statements were identified and assessed for importance according to prevalence, discordance and evidence base (stage 3). Results: Barriers and facilitators to paramedics' administration of TXA to trauma patients were represented by 11 of the 14 domains of the TDF. Important barriers included a lack of knowledge and experience with TXA (Domain: Knowledge and Skills), confusion and restrictions relating to the guidelines for TXA administration (Domain: Social/professional role and identity), a lack of resources (Domain: Environmental context and resources) and difficulty in identifying patients at risk of bleeding (Domain: Memory, attention and decision processes). Conclusions: This study presents a behavioural theory-based approach to identifying barriers and facilitators to the prehospital administration of TXA to trauma patients in the UK. It identifies multiple influencing factors that may serve as a basis for developing an intervention to increase prehospital administration of TXA.